2001
DOI: 10.1248/cpb.49.716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Constituents from the Bark of Magnolia obovata on Nitric Oxide Production in Lipopolysaccharide-Activated Macrophages.

Abstract: Inducible nitric oxide synthase (iNOS) is involved in pathological processes related to overproduction of nitric oxide (NO), and is expressed in response to pro-inflammatory agents such as interleukin (IL)-1b, tumor necrosis factor (TNF)-a and lipopolysaccharide (LPS) in various cell types including macrophages, endothelial cells, and smooth muscle cells.1) Nuclear factor (NF)-kB is a major transcription factor involved in iNOS, TNF-a, IL-1b, and IL-8 genes expression. NF-kB activation involves dissociation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 43 publications
(33 reference statements)
2
55
1
Order By: Relevance
“…In the present study, we reevaluated the modulatory effect of this compound on various NO productive conditions induced by different NO stimulatory ligands. As previously reported (12), honokiol suppressed LPS-induced NO production in a dose-dependent manner (Fig. 3B, left panel).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we reevaluated the modulatory effect of this compound on various NO productive conditions induced by different NO stimulatory ligands. As previously reported (12), honokiol suppressed LPS-induced NO production in a dose-dependent manner (Fig. 3B, left panel).…”
Section: Resultssupporting
confidence: 89%
“…2A). It is well known that honokiol suppresses NO production in macrophages (12). In the present study, we reevaluated the modulatory effect of this compound on various NO productive conditions induced by different NO stimulatory ligands.…”
Section: Resultsmentioning
confidence: 93%
“…Honokiol evidences a variety of pharmacological activities, including antioxidative (20 -22), anti-inflammatory (23,24), and antitumor activities (25,26). In this study, we attempted to determine whether the oral administration of honokiol might prevent the progression of collagen-induced arthritis (CIA), which has been used as an animal model for studies of RA pathogenesis and to evaluate potential therapeutic agents (27).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that magnolol, a compound purified from Magnolia officinalis, relaxes rat vascular smooth muscle [2], scavenges hydroxyl radicals [3], inhibits neutrophil aggregation and superoxide anion generation [4,5], suppresses the expression of vascular cell adhesion molecule-1 in endothelial cells [6], inhibits nitric oxide (NO) production in lipopolysaccharide (LPS)-activated macrophages [7]. Recently, it has been reported that the anti-inflammatory effects of magnolol are mediated through inhibition of the downstream pathway of MEKK-1 in NF-κB activation signaling [8].…”
Section: Introductionmentioning
confidence: 99%